Autonomy apparent: popular education, trade unionism and politics in the 80’s in Criciúma (SC) (Tempo e Argumento, 2010)
This article  analyzes the political trajectory of the Center of Studies, Documentation and  Popular Information of Criciúma (CEDIP) since its establishment, in 1983, until  the late 1980s. For that, the political situation of the city, besides the  articulations the Centre mantained with the Partido dos Trabalhadores, CUT,  Neighborhood Associations and the Catholic Church, was observed.
Keywords: syndicates; neighborhood aeighborhood; parties